The evaluation of Network Performance and CPU Utilization during transfer between virtual machines (Global Journal of Computer Science and Technology, 2011)
The aim of this paper is to test the performance of network communication between virtual machines during the live migration while a controlled failure occurs. Also we want to test the CPU utilization between the virtual machines in different hosts and to make a comparison with the live migration in different physical nodes. We want to introduce a script in C++ which will improve the performance of migration during the failure controller phase. Another script is built to test the CPU utilization on host computers when memory utilization is increased or decreased. We have used Httperf benchmark to test this script. Requests are sent from client machine to server machine with IPs of C class located in different hosts. These requests are some files in C which execute a multiplication of 2 square matrices with range 5, at the moment they arrive in the destination node. We have used Para-virtualization approach (Xen-Hypervisor), because it gives more flexibility and tolerance to researchers.
Keywords: Live migration; Network Communication; CPU Utilization; Controller Phase; Hypervisor